2019
DOI: 10.1002/ijgo.13007
|View full text |Cite
|
Sign up to set email alerts
|

Prospective observational study of the efficacy of mixed methylene blue compound injection for treatment of vulvar non‐neoplastic epithelial disorders

Abstract: ObjectiveTo investigate the safety and efficacy of mixed methylene blue (MB) compound injection for treatment of vulvar non‐neoplastic epithelial disorders (NNEDs).MethodsA prospective observational study among 118 women with vulvar NNEDs treated with intradermal injection of mixed MB compound at a hospital in Wuhan, China, between 2013 and 2016. Itching score, skin hypopigmentation area percentage (SHAP), and recurrence were assessed by interview and physical examination before and after treatment. Adverse ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In conclusion, the treatment effectively alleviated itching in VLS patients, and SHAP decreased significantly. Recurrence rates were relatively low [104]. PRISM may be more reliable than DLQI in capturing changes in disease-related burden post-treatment, as well as accurately quantifying baseline burden.…”
Section: Vls: Insights Into Conventional Therapeutic Approachesmentioning
confidence: 94%
“…In conclusion, the treatment effectively alleviated itching in VLS patients, and SHAP decreased significantly. Recurrence rates were relatively low [104]. PRISM may be more reliable than DLQI in capturing changes in disease-related burden post-treatment, as well as accurately quantifying baseline burden.…”
Section: Vls: Insights Into Conventional Therapeutic Approachesmentioning
confidence: 94%
“…The pathological alterations often observed in non-neoplastic lesions of the vulvar epithelium lichen simplex chronicus (LSC) and lichen sclerosus. The prevalence of the disease is 1.38%, with a high incidence in perimenopausal women ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Li et al have found that CO 2 lattice laser can remarkably improve regional cutaneous microcirculation due to the micropore thermal effect ( 1 , 2 ). Moreover, a few cases of nonneoplastic lesions of the vulvar epithelium treated with the CO 2 lattice laser have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the side effects of excessive drug use should be given attention to. Reports have shown the effectivity of laser [5], phototherapy [6], mixed methylene blue compound injection [7] and pimecrolimus cream [8] in treating VLSC. The wearing of silk fabric underwear may also be effective in the management of VLSC [9], but further research is needed.…”
Section: Introductionmentioning
confidence: 99%